Controllable Surface Reorganization Engineering on Cobalt Phosphide Nanowire Arrays for Efficient Alkaline Hydrogen Evolution Reaction. Issue 1 (24th November 2017) - Xu, Kun; Cheng, Han; Lv, Haifeng; Wang, Jingyu; Liu, Linqi; Liu, Si; Wu, Xiaojun; Chu, Wangsheng; Wu, Changzheng; Xie, Yi
Abstract: Developing highly efficient hydrogen evolution reaction (HER) catalysts in alkaline media is considered significant and valuable for water splitting. Herein, it is demonstrated that surface reorganization engineering by oxygen plasma engraving on electocatalysts successfully realizes a dramatically enhanced alkaline HER activity. Taking CoP nanowire arrays grown on carbon cloth (denoted as CoP NWs/CC) as an example, the oxygen plasma engraving can trigger moderate CoO x species formation on the surface of the CoP NWs/CC, which is visually verified by the X‐ray absorption fine structure, high‐resolution transmission electron microscopy, and energy‐dispersive spectrometer (EDS) mapping. Benefiting from the moderate CoO x species formed on the surface, which can promote the water dissociation in alkaline HER, the surface reorganization of the CoP NWs/CC realizes almost fourfold enhanced alkaline HER activity and a 180 mV decreased overpotential at 100 mA cm −2, compared with the pristine ones. More interestingly, this surface reorganization strategy by oxygen plasma engraving can also be effective to other electrocatalysts such as free‐standing CoP, Co4 N, O‐CoSe2, and C‐CoSe2 nanowires, which verifies the universality of the strategy. This work thus opens up new avenues for designing alkaline HER electrocatalysts based on oxygen plasma engraving. Abstract : A generic strategy, oxygen plasma engraving engineering, is used to trigger more efficient hydrogen evolution reaction (HER) catalytic activity on the surface of cobalt phosphide in an alkaline electrolyte. The promotion of HER activity relies on the in situ construction of a CoO x /CoP interface, where the amount of oxide can be precisely controlled to an appropriate value by the plasma engraving time.